IMPLIKASI PERALIHAN KEWENANGAN SERTIFIKASI HALAL BERDASARKAN KEPUTUSAN KEPALA BADAN PENYELENGGARA JAMINAN PRODUK HALAL NOMOR 40 TAHUN 2022 - Muhammad Pratama Mulya Sunarko; Dipo Wahjoeono (Gapenas Publisher, 2022)
Halal fatwas in one of the hundred products from Majelis Ulama Indonesia. In recent days, it become less-binding related to policy in Indonesia. Religion Ministry of Industri take over the authority of that declaration product control to accelerate timing of certification process, legalize the certainty of halal, and to maximize ecosystem development of halal in Indonesia. Through Keputusan Kepala Badan Penyelenggara Jaminan Produk Halal No.40 Tahun 2022, this transition of development has legal constitute in this country